Analisis Kesalahan Berbahasa Dalam Makalah “Proposal Bahasa Indonesia” - Chairani Dwi Putri; Abellia Najwa Nabila; Adinda Nabila; Asna Juwaira; Fadiyah Ramadani; Nazma Aliya; Wisman Hadi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Language plays an important role as a communication tool for conveying thoughts and feelings. In Indonesia, Bahasa Indonesia serves as the unifying language that brings the nation together. Language users need to master linguistic skills, including the use of standard words and punctuation, to communicate effectively. Linguistic errors, such as improper use of standard words and punctuation mistakes, often occur in academic writing. This study aims to analyze linguistic errors in the scientific paper